2018
DOI: 10.1111/jog.13667
|View full text |Cite
|
Sign up to set email alerts
|

How is the human umbilical artery regulated?

Abstract: The purpose of this review is to present an update of the main mechanisms involved in the physiological regulation of contraction and relaxation of the human umbilical artery (HUA) smooth muscle cells. A literature review was performed based on the analysis of papers available on PubMed. The most important and relevant studies regarding the regulation of the HUA are presented in this article. The vascular smooth muscle is a highly specialized structure, whose main function is to regulate the vascular tonus. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 77 publications
1
35
0
Order By: Relevance
“…They all act on the vasculature through their involvement with L-type Ca 2+ channels. In addition, the data obtained from (−)-carveol in the presence of elevated K + also support this evidence, since the contraction induced by potassium chloride (KCl) is mainly due to the influx of extracellular Ca 2+ through VOCCs, where this effect is partially inhibited by specific L-type Ca 2+ channel antagonists (LTCC) [26].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…They all act on the vasculature through their involvement with L-type Ca 2+ channels. In addition, the data obtained from (−)-carveol in the presence of elevated K + also support this evidence, since the contraction induced by potassium chloride (KCl) is mainly due to the influx of extracellular Ca 2+ through VOCCs, where this effect is partially inhibited by specific L-type Ca 2+ channel antagonists (LTCC) [26].…”
Section: Discussionmentioning
confidence: 69%
“…Elevation of [Ca 2+ ] i can also occur through the binding of external agonists such as 5-HT or His, including others, which trigger a signaling mechanism involving the activation of a complex cascade of secondary messengers. These include IP 3 and diacyl glycerol which activate internal receptors on the sarcoplasmic reticulum, which contain intracellular Ca 2+ stores (pharmacomechanical coupling) [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the effects on ion channels, several studies suggested that T exerts its vasodilatory effects by modulating different K + and/or Ca 2+ channels [15,21,[32][33][34]. The vascular tone is controlled by the ion flow, and the activation of K + channels represents the key mechanism involved in the relaxation [35,36]. This activation of K + channels causes a membrane hyperpolarization that closes the Ca 2+ channels, leading to vasorelaxation [37,38], and showing the close relationship between the channels mentioned.…”
Section: Genomic and Non-genomic Overlapping Vasodilatory Mechanisms mentioning
confidence: 99%
“…Moreover, the electrophysiological measurements using the patch-clamp technique showed that the amplitudes of the basal potassium currents in each channel are very different [ 1 , 5 ]. Currently, there are four different types of K + channels described in SMCs from the human umbilical artery: K V , K Ca , Kir, and 2-pore domain K + (K 2P ) channels ( Figure 1 ) [ 9 , 10 ]. However, the presence of intermediate-conductance Ca 2+ -activated K + channels (IK Ca ), one subtype of K Ca , has never been demonstrated [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%